Commercial Flats, Residential Breaches: Evaluating Legal Action on Misuse in Kudus (Indonesian Journal of Agrarian Law, 2024)
The phenomenon of unauthorized conversion of residential units into commercial spaces in commercial apartment buildings in Kudus Regency has become a serious issue, impacting spatial planning, comfort, and the safety of residents. This study aims to analyze the effectiveness of law enforcement by local government against violations of residential functions, identify the main obstacles, and formulate applicable solutions to improve compliance with residential use. The research employs an empirical juridical method with a case study approach in Kudus. The findings reveal that the effectiveness of law enforcement remains low due to weak supervision, the lack of strict sanctions, limited resources, and low legal awareness among the community. Additionally, overlapping regulations and insufficient inter-agency coordination exacerbate the situation. Regulatory reform, digitalization of the monitoring system, strengthening the capacity of the Owners and Residents Association (PPPSRS), and cross-sectoral synergy between government, developers, and residents are required. The recommendations of this study are expected to serve as a reference for the formulation of more effective policies and law enforcement strategies in the management of commercial apartment buildings in Indonesia.